A repertoire of failures in connecting rods for internal combustion engines, and indications on traditional and advanced design methods. (February 2016) - Strozzi, A.; Baldini, A.; Giacopini, M.; Bertocchi, E.; Mantovani, S.
Abstract: Several typical and uncommon failure modes in con-rods for internal combustion engines are commented from the stress level viewpoint. The interpretation of the fractures is supported with traditional calculations, with more advanced analytical models, and with Finite Element (FE) predictions. The repertoire of failures in a con-rod is presented by separately addressing the parts composing the con-rod itself, namely the shank, and the small and big ends. Highlights: Several typical and uncommon failure modes of connecting rods are presented. The various parts forming the con-rod are examined separately. Both analytical and numerical methods are employed to interpret the failures. A brief extension to tribological problems is included.